1989
DOI: 10.1063/1.101394
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser pumped blue-light source at 473 nm using intracavity frequency doubling of a 946 nm Nd:YAG laser

Abstract: Using intracavity frequency doubling of a diode laser pumped 946 nm Nd:YAG laser, 3.1 mW of blue output power at 473 nm was obtained. Angle-tuned, type-I frequency doubling in potassium niobate was employed, and both the KNbO3 and Nd:YAG crystals were used at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Thus, in principle, blue laser light can be generated by pumping NYAB crystals with commercial low-current laser diodes. In fact, Risk et al 15 demonstrated this blue light generation by using KNbO 3 nonlinear crystal placed inside a diode-pumped Nd 3ϩ :YAG cavity. Nevertheless, NYAB is the first material in which this sum-frequency mixing phenomenon is carried out in the same material.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in principle, blue laser light can be generated by pumping NYAB crystals with commercial low-current laser diodes. In fact, Risk et al 15 demonstrated this blue light generation by using KNbO 3 nonlinear crystal placed inside a diode-pumped Nd 3ϩ :YAG cavity. Nevertheless, NYAB is the first material in which this sum-frequency mixing phenomenon is carried out in the same material.…”
Section: Introductionmentioning
confidence: 99%
“…To make a compact system, use of solid-state lasers is promising. Historically, the principle of blue solid-state laser using intracavity SHG neodymium: yttrium aluminum garnet (Nd:YAG) laser has been discussed [16,17]. However, the stability of the frequency doubling crystal was the bottleneck for the development of a good laser which can be applied to optical equipments.…”
Section: Excitation In the Scanner Systemmentioning
confidence: 99%
“…The Cr:LiSAF crystal laser is a semiconductor laser which has been reported to be a pumpable variable-wavelength solid-state laser [1,3], and which is expected to function as an LD-pumped variable-wavelength laser due to its use of emissions across a wide range, from 780 to 1000 nm. In addition, the absorption coefficient for this crystal is high, and the pumping efficiency is high because the pump-light absorption bandwidth is extremely wide, roughly 100 nm centered at 670 nm, thereby reducing the effects of wavelength changes on the pumped semiconductor laser.…”
Section: Overall Configurationmentioning
confidence: 99%
“…In SHG lasers in the blue region, the generation of blue light at 473 nm [3] in KN (KNbO 3 ) crystals with a 946-nm fundamental wave from a Nd:YAG (Y 3 Al 5 O 12 ) crystal, and from Cr:Li-SAF (LiSrAlF 6 ) crystal in combination with LIO (LiIO 3 ) [4], KN [5], and LBO (LiB 3 O 5 ) crystals [6], has been reported. In SHG lasers in the blue region, the generation of blue light at 473 nm [3] in KN (KNbO 3 ) crystals with a 946-nm fundamental wave from a Nd:YAG (Y 3 Al 5 O 12 ) crystal, and from Cr:Li-SAF (LiSrAlF 6 ) crystal in combination with LIO (LiIO 3 ) [4], KN [5], and LBO (LiB 3 O 5 ) crystals [6], has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation